Investigation of the Emerging Nosocomial Wickerhamomyces anomalus Infections at a Chinese Tertiary Teaching Hospital and a Systemic Review: Clinical Manifestations, Risk Factors, Treatment, Outcomes, and Anti-fungal Susceptibility - Zhang, Li; Xiao, Meng; Arastehfar, Amir; Ilkit, Macit; Zou, Jun; Deng, Yuchen; Xu, Yingchun; Liao, Wanqing; Zhao, Jingjun; Fang, Wenjie; Pan, Weihua (Frontiers in Microbiology, 2021)
Wickerhamomyces anomalus is an emerging pathogen, which has been associated with clonal outbreaks and poor clinical outcomes. Despite being an important emerging yeasts species, our understanding concerning the microbiological and clinical characteristics of infections due to this species is limited. Herein, we are reporting a retrospective analysis of fungemia patients with W. anomalus from a 2100-bed hospital in Shanghai during 2014-2016. Moreover, we conducted an extensive literature review to gain a deeper clinical and microbiological insights. Detailed clinical data were recorded. Antifungal susceptibility testing (AFST) followed CLSI M27-A3 and isolates were identified using MALDI-TOF MS. In total, 13 patients were identified with a mortality rate of 38.5% (5/13). Central venous catheter, broad-spectrum antibiotic therapy, total parenteral nutrition, surgery and mechanical ventilation were the most frequently observed risk factors. Eight patients (61.5%) experienced mixed bacterial/Candida bloodstream infections and four patients developed mixed candidemia. W. anomalus isolates showed high minimum inhibitory concentrations against all azoles tested and flucytosine, while AMB showed the highest in-vitro activity. Azoles were used for 84.6% (11/13) of the cases, while 36.4% (4/11) of them died. When combining with the AFST data and the literature review, our study highlights the poor efficacy of azoles and optimal efficacy of AMB and LAMB against infections caused by W. anomalus. In conclusion, our study highlights the emerging threat of W. anomalus affecting both neonates and adults. Furthermore, our results advocate the use of AMB formulations rather than azoles among patients infected with W. anomalus. Future studies are warranted to reach a definitive consensus regarding the utility of echinocandins among such patients.